2020
DOI: 10.1111/jcpe.13342
|View full text |Cite
|
Sign up to set email alerts
|

The systemic inflammatory response following hand instrumentation versus ultrasonic instrumentation—A randomized controlled trial

Abstract: Objective: This study sought to investigate whether the immediate systemic inflammatory response following full-mouth debridement differs following use of hand compared with ultrasonic instruments.Methods: Thirty-nine periodontitis patients were randomized to treatment with full-mouth debridement using either hand or ultrasonic instrumentation completed within 24 hr. Serum and periodontal clinical parameters were collected at baseline, day 1, day 7 and day 90 post-treatment. Differences in systemic inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…In smokers with periodontal disease, nonsurgical mechanical therapy (also here not further specified) induced a significantly higher increase of IL-8 compared to non-smokers with periodontal disease [33]. When comparing hand versus ultrasonic instrumentation in terms of inflammatory markers, no differences between IL-6, CRP, and TNF-α levels at days 1 and 7 after instrumentation were discerned [17]. Also, numerous in vitro studies showed that human gingival fibroblasts secrete increased levels of IL-8 in response to LPS from P. gingivalis [3,13,24].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In smokers with periodontal disease, nonsurgical mechanical therapy (also here not further specified) induced a significantly higher increase of IL-8 compared to non-smokers with periodontal disease [33]. When comparing hand versus ultrasonic instrumentation in terms of inflammatory markers, no differences between IL-6, CRP, and TNF-α levels at days 1 and 7 after instrumentation were discerned [17]. Also, numerous in vitro studies showed that human gingival fibroblasts secrete increased levels of IL-8 in response to LPS from P. gingivalis [3,13,24].…”
Section: Discussionmentioning
confidence: 88%
“…Even though it has been well established that manual and ultrasonic instrumentation result in similar clinical outcomes in periodontitis patients [1,17,31], the two treatment modalities might influence the biofilm-cell interactions on a molecular level. Differences in biofilm removal 14 or water irrigation are likely to induce different cell responses of surrounding epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…6,29,30,31,32 Interestingly, treatment time for HI demonstrated a stronger correlation with disease severity, while ultrasonic showed a weaker correlation. 20 It could therefore be speculated that UI offers greater time saving, particularly for the treatment of patients affected by more severe periodontal disease. Limitations of such a subgroup analysis must be considered when interpreting such speculation.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a post hoc analysis using pooled data generated by two separate studies: a randomised controlled trial (RCT) and a cohort study. 20,21 Both studies had the primary outcome of investigating systemic inflammatory effects following non-surgical periodontal treatment. The current study evaluated secondary outcome data from these studies and analysed the clinical effects of non-surgical periodontal therapy by one of three approaches: hand instrumentation (HI), ultrasonic instrumentation (UI) and combination instrumentation (CI).…”
Section: Methodsmentioning
confidence: 99%
“…This study was a secondary analysis from a randomized‐controlled trial (RCT), 6 and sought to define whether the use of hand (HI) or ultrasonic instruments (UI) has differing impacts on the subgingival plaque microbiota. As such, we investigated the microbial impacts of each instrumentation technique at a range of short‐term follow‐up time points (day 1, day 7, and day 90), to establish whether such findings may translate to compositional shifts in vivo.…”
Section: Introductionmentioning
confidence: 99%